2016
DOI: 10.14238/sp14.5.2013.283-7
|View full text |Cite
|
Sign up to set email alerts
|

Cakupan Imunisasi Dasar Anak Usia 1-5 tahun dan Beberapa Faktor yang berhubungan di Poliklinik Anak Rumah Sakit Ibu dan Anak (RSIA) Banda Aceh

Abstract: Abstrak Kemoterapi diyakini efektif dalam menghambat pertumbuhan sel kanker. Namun demikian kemoterapi juga menimbulkan efek samping bagi penderita kanker, salah satunya yaitu gangguan pemenuhan kebutuhan tidur. Penelitian ini bertujuan untuk mendapatkan informasi tentang gambaran kualitas tidur anak usia sekolah yang sedang menjalani kemoterapi di rumah sakit kanker. Penelitian menggunakan metode potong-lintang dengan melibatkan 40 responden yang diambil dengan teknik total sampling. Responden mengisi kuesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
2
3
2
Order By: Relevance
“…People with good incomes have easier access to medical care. However, in this research and research done by Tahaib et al, 6 they did not find a correlation income with complete basic immunization. In Tahaib et al, 6 84% of respondents having average to higher income but still not showing any correlation.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…People with good incomes have easier access to medical care. However, in this research and research done by Tahaib et al, 6 they did not find a correlation income with complete basic immunization. In Tahaib et al, 6 84% of respondents having average to higher income but still not showing any correlation.…”
Section: Discussioncontrasting
confidence: 72%
“…However, in this research and research done by Tahaib et al, 6 they did not find a correlation income with complete basic immunization. In Tahaib et al, 6 84% of respondents having average to higher income but still not showing any correlation. In this research, we can conclude that this happened because parents already knew that they could get basic immunization for free.…”
Section: Discussioncontrasting
confidence: 72%
“…There were also influences of education of parents, especially mothers, to the completeness of their children immunization. 18 Another research conducted in district of Bangkalan concluded that a reason why parents did not bring their children to be immunized was they were afraid that their healthy children would get sick after DPT immunization. In addition, some parents who had previously immunized their children for DPT 1 felt that their children would experience KIPI again.…”
Section: Discussionmentioning
confidence: 99%
“…munisasi merupakan salah satu intervensi kesehatan masyarakat yang secara langsung mengurangi pembiayaan kesehatan. 1,2 Secara global, imunisasi telah menurunkan angka kematian dan kesakitan pada anak. 1,3 Di Indonesia, cakupan imunisasi dasar merupakan salah satu indikator pembangunan kesehatan masyarakat dan mempunyai bobot yang tinggi.…”
Section: Pendahuluanunclassified
“…1,3 Di Indonesia, cakupan imunisasi dasar merupakan salah satu indikator pembangunan kesehatan masyarakat dan mempunyai bobot yang tinggi. 2 Terdapat kekhawatiran petugas kesehatan bahwa imunisasi akan memberikan dampak merugikan pada anak dengan infeksi human immunodeficiency virus (HIV), karena risiko infeksi diseminata pada imunisasi vaksin hidup. 4 Sebagai akibatnya terjadi kegagalan dalam memberikan perlindungan terhadap populasi yang rentan.…”
Section: Pendahuluanunclassified